Implementation of sustainable marketing methods within the context of the Czech market - Rašková, Adéla; Gburíková, Alžbeta; Rešovská, Barbora; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2024)
Escalating climate change, lack of waste regulation, social issues and clothing waste pollution pose grave threats to our planet, people, and future. This crisis impacts everyone, demanding action across all sectors and industries. This bachelor thesis presents aspects in which marketers can integrate more sustainable and responsible actions into their strategies and evaluates the operational aspects of the Czech brand with sustainability goals – Freshlabels. To assess the effectiveness of Freshlabels' sustainability efforts, this thesis analyses the brand's behaviour using the 'Revisiting the 7 Ps through Responsible Sustainable Marketing Lens' framework. Additionally, the target customer group's perspective is incorporated through interviews. In conclusion the research revealed customers and companies focus predominantly on sustainability of the sold product rather than the comprehensive sustainable marketing practises. Interviews further reveal that while Freshlabels actively promotes its commitment to sustainable fashion within the Czech Republic, their primary emphasis remains on ensuring the profitability and longevity of the company. True sustainable marketing principles advocate for placing environmental and social concerns on par with profit for an optimal outcome.
Vedoucí práce: Alžbeta Gburíková
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: multimédia v ekonomické praxi [obor bakal. práce]; bakalářské práce; bachelor's theses